Evidence for M2 and M3 Muscarinic Receptor Involvement in Cholinergic Excitatory Junction Potentials Through Synergistic Activation of Cation Channels in the Longitudinal Muscle of Mouse Ileum - Hayato Matsuyama; Yasuyuki Tanahashi; Takio Kitazawa; Masahisa Yamada; Seiichi Komori; Toshihiro Unno (Elsevier, 2013)
Cholinergic nerve-mediated excitatory junction potentials (EJPs) in the longitudinal muscle of mouse ileum were characterized by using M2 or M3 muscarinic receptor-knockout (KO) mice and 1-[β-[3-(4-methoxyphenyl)propoxy]-4-methoxyphenethyl]-1H-imidazole hydrochloride (SK&F 96365) and pertussis toxin (PTX). EJPs evoked by electrical field stimulation (EFS) in wild-type preparations, initially determined to be cholinergic in origin using tetrodotoxin, atropine, and eserine, were profoundly depressed after SK&F 96365 treatment known to block muscarinic receptor-operated cation channels. A similar depression of the EJPs was also observed by PTX treatment, which is predicted to disrupt M2-mediated pathways linked to cation channel activation. In M2-KO mouse preparations, cholinergic EJPs were evoked by EFS with their relative amplitude of 20% - 30% to the wild-type EJP and strongly inhibited by SK&F 96365. No cholinergic EJP was seen in M3-KO as well as M2/M3 double-KO preparations. The results suggest that the wild-type cholinergic EJP is not a simple mixture of M2 and M3 responses, but due to synergistic activation of cation channels by both M2 and M3 receptors in the murine ileal longitudinal muscle. Keywords:: muscarinic receptor, smooth muscle, nonselective cation channel, excitatory junction potential (EJP), small intestine